A Short Review of Irradiated Peanut Ink - Othman, Siti Amira; Hafizan Sabturo, Noraisyah (Journal of Advanced Industrial Technology and Application, 2022)
Today’s ink is not a good choice for long-term use because it contains higher levels of volatile organic compounds (VOCs). Surprisingly, the notion of making ink out of vegetable oils was one of the best inventions for the development of ink in the world because it was an environmentally friendly ink. The impact of radiation on the qualities of peanut oil and its utility as a consumer product will be discussed and information will be provided in this review study. The qualities of the oil will be improved by using radiation, and it can be used in community products. Nonetheless, while this sort of ink made from peanut oil is less harmful, its capabilities needed to be enhanced.